ECHOES OF PARADISE: ANALYSING 21ST CENTURY RENDERINGS OF SOUND IN PARADISO 30 (Italiano LinguaDue, 2025)
The article compares the outcomes of 21st century English translations of Dante’s Divine Comedy, specifically in terms of sound, by analysing the interplay of macro and micro choices made by translators. How is the sound of Paradiso 30 rendered into English as determined by the macro and micro choices in 21st century translations? Defining a corpus of five translations of Paradiso 30, each chosen for its unique English variant and distinct translation strategy, the analysis closely examines each translator’s macro and micro choices within the context of translator’s notes and introductions. This approach evinces how translators navigate the challenges of the original text with the nuances of the target language, especially in terms of sound. The results reveal a diverse range of translation losses and compensations, determined by the translator’s approach and the limitations of the English language. Overall, this research analyses the intricate choices translators make to convey sound, particularly when translating literary classics. The diversity of translation outcomes highlights the enduring appeal of Dante’s work and the continued exploration of its nuances by contemporary translators. Echi del Paradiso: analisi della resa sonora dei traduttori del XXI secolo in Paradiso 30L'articolo confronta i risultati delle traduzioni inglesi del XXI secolo della Divina Commedia, in particolare in termini di suono, analizzando l’interazione delle scelte macro e micro operate dai traduttori. Come viene reso in inglese il suono di Paradiso 30, determinato dalle scelte macro e micro delle traduzioni del XXI secolo? Definendo un corpus di cinque traduzioni di Paradiso 30, ciascuna scelta per la sua unica variante inglese e per la sua distinta strategia di traduzione, l’analisi esamina da vicino le scelte macro e micro di ciascun traduttore nel contesto delle note traduttive e delle introduzioni. Questo approccio evidenzia come i traduttori riescano ad affrontare le sfide del testo originale con le sfumature della lingua bersaglio, soprattutto in termini di suono. I risultati rivelano una vasta gamma di perdite e compensazioni nella traduzione, determinate dall’approccio del traduttore e dai limiti della lingua inglese. Nel complesso, questa ricerca analizza le scelte che i traduttori fanno per trasmettere il suono, in particolare quando traducono i classici della letteratura. La diversità dei risultati della traduzione evidenzia il fascino duraturo dell’opera di Dante e la continua esplorazione delle sue sfumature da parte dei traduttori contemporanei.